The Urgency of Implementing Restorative Justice in Handling Juvenile Crime: A Study of the Principles of Humanity and Justice - Saida Flora, Henny; Paminto, Saptaning Ruju; Salmon, Harly Clifford Jonas (Ipso Jure, 2026)
Crimes committed by juveniles are a serious problem that requires comprehensive handling, prioritizing the principles of humanity and justice. The conventional retributive approach to criminal law is considered inappropriate for the characteristics of adolescent psychological development and their rehabilitation needs. This article aims to examine the urgency of implementing restorative justice in handling juvenile crime in Indonesia from the perspective of humanity and justice. The research method used is normative legal research with statutory, conceptual, and comparative approaches. The results of the study indicate that restorative justice provides a more humane framework for resolution because it prioritizes restoring relationships between perpetrators, victims, and the community, rather than simply retaliation. This approach aligns with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which prioritizes diversion and the best interests of children. The application of restorative justice has been proven to reduce recidivism rates, encourage perpetrator responsibility, and restore victims' dignity more effectively than conventional punishment. This study concludes that restorative justice is not merely an alternative but a necessity in a just and humane juvenile criminal justice system